Pengaruh bauran pemasaran terhadap loyalitas konsumen pada alfamart Banjaran Kabupaten Majalengka - Patimah, Empat; M. Iqbal Nurfauzan (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
The purpose of this research is to collect data and information about the influence of the marketing mix on customer loyalty at Alfamart Banjaran, Majalengka Regency. Then the data obtained will be poured into writing a thesis as one of the requirements for the preparation in getting a bachelor of management degree. The independent variable is the marketing mix affecting consumer loyalty as the dependent variable. This research was conducted at Alfamart Banjaran, Majalengka Regency. The method of data collection in this study was a questionnaire filled out by respondents, namely customers of Alfamart Banjaran, Majalengka Regency. Sampling as many as 93 respondents in this study using a simple sampling method. The analysis used in this research includes analysis of validity test, reliability test, linear regression analysis, correlation analysis and coefficient of determination, hypothesis testing t-test. The results of hypothesis testing indicate that there is a positive and significant influence on the marketing mix variable on customer loyalty at Alfamart Banjaran, Majalengka Regency. This is indicated by the t-count value, which is greater than the t-table value, namely (9.5662 > 1.66177). The magnitude of this value indicates that the marketing mix has a significant effect on customer loyalty. The analysis results also obtained the value of the correlation coefficient (r) of 0.7081, which means that the influence of the marketing mix (Marketing Mix) on customer loyalty is strong. While the coefficient of determination (r2) obtained is 0.5014, indicating a positive influence of the marketing mix (Marketing Mix) on customer loyalty, this also means that customer loyalty satisfaction is influenced by the marketing mix variable (Marketing Mix) of 50.14%. In comparison, the rest (49.86%) is controlled by other variables that are not included in the analysis of this hypothesis test. The regression line equation obtained in this analysis is Y = 0.28 + 0.43X. This indicates that if the marketing mix increases by 1 unit, then customer loyalty also increases by 0.43.